Gamification and civic engagement in digital government applications: a review - Santos, Alysson Diniz dos; Aquino, Felipe Rocha de; Furtado, Lara Sucupira; Silva, Ticiana Coelho da; Cruz, Lívia (Anais do Latin American Symposium on Digital Government (LASDiGov); 2021: Anais do IX Workshop de Computação Aplicada em Governo EletrônicoDO - 10.5753/wcge.2021.15986, 2021)
In the context of Human Computer Interaction, engagement might be seen as a reflection of users' involvement and interaction with a digital system. To digital government initiatives, civic engagement refers to the ways in which citizens participate in the life of a community, in order to improve conditions for others or to help shape the communitys future. Recent studies have approached civic engagement harnessed by gamification, i.e. the adoption of game elements in non-game contexts. In this context, the goal of this research is to investigate which gamification studies and features have been applied to civic engagement initiatives. This study reviews current literature, looking for the relationship between civic engagement and how it has been applied to the Human Computer Interaction context.